解方程 6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 02:10:13
解方程6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)解方程6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)解方程6X+7(2X+3)(2X-3
解方程 6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)
解方程 6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)
解方程 6X+7(2X+3)(2X-3)=4+28乘(X-二分之一)(X+二分之一)
7x+7(4x²-9)=4+28(x²-1/4)
7x+28x²-63=4+28x²-7
7x=60
x=60/7
解方程(x-2)/(x-3)-(x-3)/(x-4)=(x-5)/(x-6)-(x-6)/(x-7)
解方程(x+1/x+2)-(x+2/x+3)=(x+5/x+6)-(x+6/x+7)
解方程:x+2/x+1-x+3/x+2=x+6/x+5-x+7/x+6
解分式方程:(x+1)/(x+2)+(x+6)/(x+7)=(x+2)/(x+3)+(x+5)/(x+6)
解分式方程: (x-1)/(x-2)+(x-6)/(x-7)=(x-2)/(x-3)+(x-5)/(x-6)
解方程 x+2/x+1+x+8/x+7=x+6/x+5+x+4/x+3
解方程 (x+2)/(x+1) - (x+4)/(x+3)=(x+6)/(x+5)-(x+8)/(x+7)
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
解方程:(2x+3)+(x-7)(x+6)=x²-10解方程:x(2x+3)+(x-7)(x+6)=x²-10
解方程:7/x^2+x+3/x^2-x=6/x^2-1
解方程:7/x^2+x-6/x^2-1=3/x-x^2
解方程:7/x^2+x-2/x-x^3=6/x^2-1
7x(x-6)+3x=4x(2x+5)怎么解这个方程
1x+2x+3x+4x+5x+6x+7x+8x+9x+10x+11x+12x+13x+14x+15x=550必须用解方程
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
x/(x-2)+(x+1)/(x-6)=2x/(x-3) 解分式方程